Respuesta :

Answer:

7x - 35 + 12 - 2x = 12

Step-by-step explanation:

Distribution is the first step. Multiply 7 to x and -35. And multiply 2 to 6 and -x. That gives you the answer 7x - 35 + 12 - 2x = 12.

The equivalant expression is 7x - 35 + 12 - 2x = 12.

We have given expression is 7x - 35 + 12 - 2x = 12

We have to determine the

The following is equivalent to 7(x-5)+2(6-x)=12

What is the distribution property?

The distributive property of binary operations generalizes the distributive law, which asserts that equality is always true in elementary algebra.

Distribution is the first step.

Multiply 7 to x and -35. And multiply 2 to 6 and -x.

That gives you the answer

7x - 35 + 12 - 2x = 12.

To learn more about the expression visit:

https://brainly.com/question/723406

#SPJ2